The harvested energy using MFCs by enriching saline-alkali tolerant microorganisms from biogas slurry - Sheng-chao Gao; Zhen Zhang; Yong-dong Li; Zhao-ying Su; Jin-song Dong; Ru-meng Zhang; Wen Zhou; Hong-xia Ni; Yi Chen; Ying Liu (iScience, 2025)
Summary: Exoelectrogenic biofilms is crucial for the energy generation and wastewater treatment by bioelectrochemical systems. In this study, two kinds of saline-alkali tolerant mixed exoelectrogenic cultures were enriched from biogas slurry. These mixed exoelectrogens produced current densities of 1,034 ± 30 and 974 ± 53 μA·cm−2, which were 1.68 and 1.58 times higher than G. sulfurreducens PCA at pH 9.0, respectively. Under alkaline conditions with the addition of 1.5% NaCl, the maximum current densities for BS-N2 (546.66 ± 139.20 μA·cm−2) and BS-O2 (583 ± 22.91 μA·cm−2) were about 2.45 and 2.61 times higher than G. sulfurreducens PCA, respectively. The BS-O2 exhibited a high power density of 1,109 ± 115 mW·m−2 at pH 9.2 in a microbial fuel cell. The community analysis revealed Proteobacteria as the predominant phylum, with Firmicutes and Bacteroidetes as the dominant families within the biofilms. These findings provide valuable insights for further research on exoelectrogenesis in challenging environments.